Attention-deficit hyperactivity disorder’s diagnostic dilemma. - Ong, Qiu Xuan. (2013)
Attention-Deficit Hyperactivity Disorder (ADHD) has become the term that adults conveniently attach to children with age-inappropriate behaviors. Over time, excessive advertising by pharmaceutical companies and mediums of media have “popularized” the disorder. This has increased the general public’s awareness of the disorder, but it also contributed to the over-use of the diagnosis as an easy stick-on label that individuals append on a child. Similarly, clinicians have found an increasing number of children to be diagnosed with the disorder. Consequently, this has prompted the discussion of whether ADHD is over diagnosed. Various research groups have debated the utility of the differential diagnosis and have derived disparate conclusions. This report reviews the Diagnostic Statistical Manual Fourth edition, Text Revision’s (DSM-IV-TR) utility as a categorical diagnostic instrument for diagnosing ADHD amongst children. First, we examine the history of DSM-IV-TR and its developments, followed by an extensive discussion of its utility in epidemiologic and research settings. We then establish that the use of a dimensional diagnostic approach may be more effective in identifying ADHD in children and will result in better treatment outcomes. Further, we proffer that the change from a differential diagnostic approach to a dimensional one is plausible . Hence, this review will suggest a plausible diagnostic approach to bridge the differences between the categorical and dimensional approaches. We then compare our model with existing approaches such as the CBCL and the upcoming DSM-5 and offer our considerations for future editions of the DSM.